The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3727/096368908785096024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Serum with Fetal Bovine Serum for Expansion and Differentiation of Human Synovial MSC: Potential Feasibility for Clinical Applications

Abstract: The aim of this study was to evaluate the effect of human serum (HS) on growth and differentiation capacity of human synovium-derived mesenchymal stem cells (MSC) in comparison to cells grown in fetal bovine serum (FBS). Human MSCs were isolated from the synovium of knee joints of three donors and the cells were cultured individually in varying concentrations of allogenic HS or FBS. Bovine MSCs were isolated from synovium and cultured in the same manner. Cell proliferation was assessed by the tetrazolium assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 24 publications
3
78
0
Order By: Relevance
“…34,35 An in vitro chondrogenesis assay of rat MSCs demonstrated that pellets derived from synovium had superior chondrogenic potential, 36 which they retained chondrogenic potential only after a few passages. Tateishi et al 37 demonstrated allogenic human serum is superior for culture of human synovium-derived MSCs in terms of cellular expandability without losing chondrogenic differentiation capacity, though the underlying mechanisms remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 An in vitro chondrogenesis assay of rat MSCs demonstrated that pellets derived from synovium had superior chondrogenic potential, 36 which they retained chondrogenic potential only after a few passages. Tateishi et al 37 demonstrated allogenic human serum is superior for culture of human synovium-derived MSCs in terms of cellular expandability without losing chondrogenic differentiation capacity, though the underlying mechanisms remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mesenchymal stem cells (MSC) is an attractive option as these cells have a long lifespan and are not fully differentiated, suggesting that they could be tolerated from one individual to another. The use of human serum instead of serum of animal source, seems to have a direct and a positive effect on the phenotype of human synovium-derived mesenchymal stem cells (MSC), (Tateishi et al, 2008). The results of this study indicated that human serum (HS) is superior for the culture of human MSCs compared with fetal bovine serum (FBS) in terms of cellular expandability, without losing chondrogenic or osteogenic differentiation capacity.…”
Section: Cell-seeded (Stem Cells Autologous Cell Sources) or Acellulmentioning
confidence: 90%
“…FBS, which contains a pool of undetermined factors and components, caused the differentiation of BCSCs. Although FBS is an essential component of cell culture medium, it has been shown to cause differentiation of certain kinds of stem cells such as neural and embryonic, as well as germ cells (Bettiol et al, 2007;Franke et al, 2014;Hung and Young, 2006;Tateishi et al, 2008;Zahir et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In some recent publications, oxygen concentration has been shown to also affect drug resistance (Crowder et al, 2014;Samanta et al, 2014) and stemness of BCSCs (Mimeault and Batra, 2013;van den Beucken et al, 2014). Therefore, in this study we investigated the effects of components of media (FBS and growth factors) and oxygen concentration on spontaneous differentiation of BCSCs in vitro.…”
Section: Introductionmentioning
confidence: 99%